The Development of Settlement in Code River Dwelling from Traditional Myth Forward Modern Functional in Yogyakarta - Soekadri, Soekadri (Forum Geografi, 2002)
It is interesting to see the Phenomenon of houses improvement in the Cultural Geography and District Development point of view since 1965, during Development Order era until Rqhrmation Order (nowadays) in Kampung Gembalalean Bawah, Cokrodirjan Kalurahan Suryatmajan and Kampung Ledok Tukangan Tegalpanggung. The objective of this study is to ï¬gure out whether it is true that there is a relationship and influence between family education, occupation, family income, religion, orientation, society institution (LKMU) and also nature resource such as land and water toward the indication of dwelling environment development which are also as a cultural changing.The method that is used in this study is Purposive Sampling which determines the location survey. The source in this study can be divided into two parts, those are the primary data and secondary data The primary data are obtained by applying interview to 40 heads of family from Kampung Gemblalean Bawah and Cokrodirjan, and 40 heads of family from kampung Ledok Tukangan. The secondary data are from the related institutions.In the analisys the writer needs to employ the multiple regresion and correlation technic to deï¬ne the relationship and influence between the social economy factors and the culture. The result of this study shows that since 1965, during the development order, the development of houses that is considered as the culture phenomenon is in progress.The analisys shows that there is a significant relationship on the family income factor in Tegalpanggung but there is not in Suratmajan. The multiple regression analisys displays that it has a positive relationship on all factors including social economy factor in both locations, but it becomes doubtful after each R Square analisys contributes more or less 20 percent only. It is because of the historical background of society in both locations. They were migrants and now live in their ancestral hams. One of their typical characteristics is that they still have an orientation to their origin places. Therefore the houses they live in now tend to he temporary houses for short-term settlement.TheAMD Program (one of Indonsian Government Program which concerns Indonesian Army/ABRI to make a community service in the village), could manipulate the condition by guiding the people to carry out the public necessity such as ï¬ood preventive. The ï¬ood always threatens the sojourn, dwelling house and their environment with destruction. This program is eï¬ective to inï¬uence the people mattitude and behavior to make a forward movement in house renovation and environment maintenance. The rsult emphasizes a new atmosphere of cultural dimension, which is caused by a power distance, in this case, interest group, so that enables the people to have culture progress.